Isotopic and elemental characterisation of Slovenian apple juice according to geographical origin: Preliminary results. (15th July 2016) - Bizjak Bat, Karmen; Eler, Klemen; Mazej, Darja; Mozetič Vodopivec, Branka; Mulič, Ines; Kump, Peter; Ogrinc, Nives
Highlights: Stable isotope and elemental parameters differentiate between five geographical regions in Slovenia. The prediction ability is 83.9%. LDA was found to be the most appropriate method for geographical origin discrimination. Good separation was also obtained between cultivars. Abstract: This study examined the applicability of stable isotope and multi-element data for determining the geographical origin of fresh apple juices. Samples included three apple cultivars (Idared, Golden Delicious and Topaz) harvested in 2011 and 2012 from five different geographical regions of Slovenia. Regional discrimination of the juice samples was most successful when using linear discriminant analysis (LDA) and taking into account the following parameters: δ 2 H and δ 18 O content of juice water; δ 15 N and δ 13 C content of the pulp, (D/H)I and (D/H)II in ethanol and the concentration of S, Cl, Fe, Cu, Zn and Sr. Overall prediction ability was 83.9%. The factors that best distinguished the different types of cultivar were the δ 2 H and δ 18 O content of fruit juice water; the δ 13 C and (D/H)I content of ethanol; and the concentration of S, Mg, K, Cu, and Ti. Prediction ability, taking into account all ten parameters, was 75.8%.